Prévenues et détenues logées à la même enseigne, l’exemple des prisons de Burnaby et Tanguay - McLean, Julia (Criminologie, 1995)
This article addresses the issue of the particular categories and degrees of constraints imposed upon pre-trial and convicted female inmates in Canadian institutions, focusing on two of those referred to as examples, Maison Tanguay in the province of Québec and the Burnaby Correctional Centre for Women located in British Columbia. It describes the conditions faced by women, incarcerated for a more or less long term period, and attempts to portray some reasoning as to why a pre-trial inmate must be subjected to similar or worse prison conditions as that of a convicted fellow. In order of do so, the author considers studies such as Biron (1992), Heidensohn (1985) and Bertrand (I994). The article concludes by indicating that due to the incertainty of her situation (would the suspect be convicted, when and what would be the sentence?) a pre-trial inmate may suffer additional constraints compared to an inmate convicted to prison for several years.